Description of the final instar larva of Argia serva Hagen in Selys, 1865 (Odonata Coenagrionidae) - PALACIO,ALEJANDRO DEL (2018)
Abstract The American genus Argia, with more than 100 species described, is the most speciose genus of Odonata in the world. In this contribution, the final stadium larva of Argia serva, the southernmost distributed species of Argia, is described and diagnosed based on reared material from Martín García island, Buenos Aires, Argentina. The larva of this species can be easily separated from the other Argentinean Argia by the following combination of characters: sternum of S8 covered with spines (bare in A. translata); antennal segment 3 longer than 1+2 (equal to or shorter than 1+2 in A. joergenseni and A. jujuya); palpal setae absent (present in A. croceipennis). A key to the known larvae of Argia of the Southern Cone is provided.